Dukungan Keluarga, Petugas Kesehatan, Pengetahuan Ibu dan Pengaruhnya terhadap Kesiapan Menghadapi Kehamilan di RSUD Mampang Prapatan Tahun 2022 - Ati Winingsih (MPI Press, 2023)
Introduction: Pre-pregnancy preparation is a broad term that refers to the process of identifying multiple risks to reduce risks through education, counseling and appropriate interventions before pregnancy. Family support, health workers, and knowledge are one of the factors that can affect the mother's readiness to face pregnancy. Objectives: This study aims to determine the effect of family support, health workers, and knowledge on readiness to face pregnancy at Mampang Prapatan Hospital in 2022. Method: Using descriptive analytics with a cross-sectional approach. The population of this study was 32 pregnant women and the sampling technique used was total sampling with a total sample of 32 people. The research instrument used a questionnaire and the data collected was tested using the chi-square statistical test. Result: The results of the research conducted showed that there was a significant effect between family support and readiness to face pregnancy, a P-value of 0.024 was obtained, the support of health workers with readiness to face pregnancy obtained a P-value of 0.006, and knowledge with readiness to face pregnancy obtained a P-value of 0.005. Conclusion: The conclusion of this study is that there is an effect of family support, health workers, and mothers’ knowledge on readiness to face pregnancy at Mampang Prapatan Hospital in 2022.